2007
DOI: 10.1158/1078-0432.ccr-06-2950
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linking of Signal Transducer and Activator of Transcription 3—A Molecular Marker for the Photodynamic Reaction in Cells and Tumors

Abstract: Purpose: Photodynamic therapy (PDT) depends on the delivery of a photosensitizer to the target tissue that, under light exposure, produces singlet oxygen and other reactive oxygen species, which in turn cause the death of the treated cell. This study establishes a quantitative marker for the photoreaction that will predict the outcome of PDT. Experimental Design: Cells in tissue culture, murine s.c. tumors, and endobronchial carcinomas in patients were treated with PDT, and the noncleavable cross-linking of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 22 publications
1
43
1
Order By: Relevance
“…Because it has been proposed that cell transformation induces an intrinsic resistance program to chemotherapy (56), we speculate that cdk5-STAT3 provides cancer cells with intrinsic resistance capacities due to enhanced Eme1 expression and that this a corollary of cell transformation. We propose that the early detection on tumor biopsies of the cdk5-STAT3 oncogenic pathway, both of its phosphorylation status and of its target genes, will provide oncologists with a resistance profile indicative of tumors that will fail to respond to chemotherapy (15,57). In addition, we also propose that STAT3 inhibitors, which are emerging as new targeted cancer therapies (2,57,58) should be tested in clinical trials in combination with irinotecan to reduce DNA repair and enhance the efficiency of genotoxic treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Because it has been proposed that cell transformation induces an intrinsic resistance program to chemotherapy (56), we speculate that cdk5-STAT3 provides cancer cells with intrinsic resistance capacities due to enhanced Eme1 expression and that this a corollary of cell transformation. We propose that the early detection on tumor biopsies of the cdk5-STAT3 oncogenic pathway, both of its phosphorylation status and of its target genes, will provide oncologists with a resistance profile indicative of tumors that will fail to respond to chemotherapy (15,57). In addition, we also propose that STAT3 inhibitors, which are emerging as new targeted cancer therapies (2,57,58) should be tested in clinical trials in combination with irinotecan to reduce DNA repair and enhance the efficiency of genotoxic treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Photodynamic therapy reduced the STAT3 response to IL-6 by 90%, but that to Hyper-IL-6 only by 30%. The presence of crosslinked STAT3 complexes, which are known to correspond to absorbed PDT dose (Liu et al, 2004;Henderson et al, 2007), indicated that the individual cultures within each experimental group had received comparable PDT exposure. Taken together, this suggests a preferential PDTmediated inactivation of IL-6Ra over gp130, the latter still being able to engage the IL-6/sIL-6Ra complex.…”
Section: Conditioned Medium From Pdt-treated Hela Cells Induces Macromentioning
confidence: 99%
“…The level of STAT3 crosslinking in tumor tissue subjected to PDT in situ was determined by excising the tumor immediately following light treatment, mincing tumor tissue and extracting proteins by sonication in RIPA buffer. Aliquots of cleared extracts, containing 20 µg proteins, were separated under denatured condition on 6% SDS polyacrylamide gels and analyzed by immunoblotting for the level of homodimeric STAT3 relative to total STAT3 as reported previously [22,52].…”
Section: Stat3 Crosslinkingmentioning
confidence: 99%
“…The crosslinking of STAT3 is strictly proportional to the delivered light dose and PS dose and thus can be used as a molecular marker for the cumulative photoreaction [22]. Quantification of vascular parameters before and during PDT is desired for monitoring and optimizing the PDT response that is manifested by the level of STAT3 crosslinking at the end of light treatment.…”
Section: Introductionmentioning
confidence: 99%